Reﬂections of a Canadian RNFA Past, Present and Future - Groetzsch, Gra (Operating Room Nurses Association of Canada Journal, 1998)
At present I am one of three formally trained Registered Nurse First Assistants (RNFA) in Canada and the only one employed in that capacity. To become an RNFA one must be a registered nurse with a minimum of two years experience in perioperative nursing, and must have obtained perioperative certification (CNOR, CPN(C)), Advanced Cardiac Life Sup- port (ACLS) and/or Basic Cardiac Life Support (BCLS) certification, letters of recommendation and liability insurance. I am currently insured through an American carrier affiliated with AORN. At present, a degree is not necessary but after 1999 in the United States a degree will be required to write the perioperative certification examination(CNOR) and hence to become an RNFA.